2014
DOI: 10.1044/2014_aja-13-0060
|View full text |Cite
|
Sign up to set email alerts
|

Higher Prevalence of Autoimmune Diseases and Longer Spells of Vertigo in Patients Affected With Familial Ménière's Disease: A Clinical Comparison of Familial and Sporadic Ménière's Disease

Abstract: PURPOSE This study compared clinical features, predisposing factors, and concomitant diseases between sporadic and familial Ménière's disease (MD). METHOD Retrospective chart review and postal questionnaire were used. Participants were 250 definite patients with MD (sporadic, n =149; familial, n = 101) who fulfilled the American Academy of Otorhinolaryngology-Head and Neck Surgery (1995) criteria. RESULTS On average, familial patients were affected 5.6 years earlier than sporadic patients, and they suffered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
1
9
2
1
Order By: Relevance
“…4,6,29,30 Genetic predispositions are likely to be associated with autoimmunity and migraines in patients with MD, which shows a higher prevalence in patients with BMD. 5,31 Our results are not similar to these results from Caucasian populations (Table IV); the prevalence of familial MD and vestibular migraine are not higher in BMD than in patients with UMD. Recent studies with large European and Asian populations reported that the frequency of BMD was not higher in patients with familial MD than in those with sporadic MD.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…4,6,29,30 Genetic predispositions are likely to be associated with autoimmunity and migraines in patients with MD, which shows a higher prevalence in patients with BMD. 5,31 Our results are not similar to these results from Caucasian populations (Table IV); the prevalence of familial MD and vestibular migraine are not higher in BMD than in patients with UMD. Recent studies with large European and Asian populations reported that the frequency of BMD was not higher in patients with familial MD than in those with sporadic MD.…”
Section: Discussioncontrasting
confidence: 97%
“…A higher prevalence of familial MD in patients with BMD has been reported, and immune‐related genes, such as allelic variants of TLR10, polymorphisms of PTPN22, and the HLA‐DRB*1101 allele, have been identified as candidates for causing BMD in several studies . Genetic predispositions are likely to be associated with autoimmunity and migraines in patients with MD, which shows a higher prevalence in patients with BMD . Our results are not similar to these results from Caucasian populations (Table ); the prevalence of familial MD and vestibular migraine are not higher in BMD than in patients with UMD.…”
Section: Discussioncontrasting
confidence: 90%
“…The clinical features that were significantly different between the sporadic and familial MD in this study were the age of onset and prevalence of migraines. These findings are also common in Caucasian populations, as reported in other studies . Although the age of onset was significantly earlier in definite familial MD patients than in sporadic cases, it was not significantly different between familial MLS and sporadic cases ( P = .05).…”
Section: Discussionsupporting
confidence: 88%
“…These findings are also common in Caucasian populations, as reported in other studies. 10,11,17 Although the age of onset was significantly earlier in definite familial MD patients than in sporadic cases, it was not significantly different between familial MLS and sporadic cases (P 5.05). However, the P value for significance was borderline, but may have been significant if a larger patient pool were enrolled.…”
Section: Discussionmentioning
confidence: 88%
“…33,34 Autoimmune MD Animal studies demonstrated the induction of antibodies production by the inner ear, giving further evidence that the endolymphatic sac has an immune function. 35,36 Human studies have demonstrated the presence of autoantigens against the inner ear, both in MD and in autoimmune inner ear disease. Regarding MD, several hypotheses have been proposed to explain the appearance of autoimmune responses in the inner ear, including the appearance of cross-reactions with shared epitopes between inner ear proteins and microbial proteins, the induction of damage associated with sustained high levels of cytokines and chemokines, or the presence of immunogenic factors producing a persistent inflammatory response in the inner ear.…”
Section: Genetic MDmentioning
confidence: 99%